IDENTIFICATION OF LACTIC ACID BACTERIA (BAL) FROM THE INTESTINES OF Pangasianodon hypophthalmus THAT WAS FEEDED BY FERMENTED HERBAL AND THE ABILITY TO INHIBIT Aeromonas hydrophila BACTERIA - mASTUTI, Rini; Syawal, Henni; Luskityowati, Iesje (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2022)
Lactic acid bacteria can improve digestibility because they can be absorbed directly by the body. The purpose of this research was to obtain lactic acid bacteria types from the intestines of striped catfish (Pangasionodon hypophthalmus) that had been fed fermented herbal feed. This research was conducted from June 2019 to April 2020. The treatment used in this research was with different doses and stocking densities. The test was carried out using the disc diffusion method or the Kirby-Bauer method, which was done by measuring the inhibition zone around the paper disc. Identification of LAB was carried out by phenotypic and genotypic. The results showed that as many as four of the selected isolates were able to inhibit the growth activity of the pathogenic bacteria Aeromonas hydrophila. Isolates with code K had an inhibition zone of 6.7 mm against A.hydrophila, an inhibition zone of 7.5 mm for P1D2 isolates, P2D1 isolates had an inhibition zone of 7.0 mm, P2D2 isolates had an inhibition zone of 7.8 mm. Types of LAB that were identified phenotypically and genotypically include Lactobacillus casei, L.plantarum, and L. acidhopilus